Some reproductive characteristics of the blotched picarel Spicara maena (Perciformes: Centracanthidae) from Saros Bay, Northern Aegean Sea, Turkey - Cengiz, Özgür (Revista de Biología Marina y Oceanografía, 2019)
This study was carried out, monthly, in the Saros Bay (Northern Aegean Sea, Turkey) between January 2015 and December 2015. The gonadosomatic index (GSI) and absolute fecundity (Fa) of the blotched picarel (Spicara maena) were analyzed . GSI values suggested the spawning period of S. maena was from April to June. The relations between the absolute fecundity and total length (TL), total weight (TW) and age (A) of the blotched picarel females were estimated as Fa= 287.52TL1.40, Fa= 153.33TW + 6,680.9 and Fa= 2,407.5A + 5,289.6, respectively. The present study contributes to the reproductive biology of S. maena by reporting the first data about the fecundity of the species for the Aegean Sea.